Clinical factors associated with adverse clinical outcomes in elderly versus non-elderly COVID-19 emergency patients: a multi-center observational study - Puchongmart C. (2023)
Background: The COVID-19 pandemic has caused over 6 million deaths worldwide. The elderly accounted for a large proportion of patients with their mortality rate largely higher than the non-elderly. However, limited studies have explored clinical factors associated with poor clinical outcomes in this important population. Therefore, this study aimed to determine factors independently associated with adverse clinical outcomes among COVID-19 elderly patients. Methods: We conducted a multicenter observational study at five emergency departments (EDs) in Thailand. Patients over 18 years old diagnosed with COVID-19 between January and December 2021 were included. We classified patients into elderly (age ≥ 65 years) and non-elderly (age < 65 years). The primary clinical outcome was in-hospital mortality. The secondary outcomes were endotracheal intubation and intensive care unit admission. We identified independent factors associating with these outcomes both in the whole population and separately by age group using multivariate logistic regression models. Results: A total of 978 patients were included, 519 (53.1%) were elderly and 459 (46.9%) were non-elderly, and 254 (26%) died at hospital discharge. The mortality rate was significantly higher in the elderly group (39.1% versus 14.3%, p<0.001)). In the elderly, age (adjusted odds ratio (aOR) 1.13; 95% confidence interval (CI) 1.1—1.2; p<0.001), male sex (aOR 3.64; 95%CI 1.5–8.8; p=0.004), do-not-resuscitate (DNR) status (aOR 12.46; 95%CI 3.8–40.7; p<0.001), diastolic blood pressure (aOR 0.96; 95%CI 0.9–1.0; p=0.002), body temperature (aOR 1.74; 95%CI 1.0–2.9; p=0.036), and Glasgow Coma Scale (GCS) score (aOR 0.71; 95%CI 0.5–1.0; p=0.026) were independent baseline and physiologic factors associated with in-hospital mortality. Only DNR status and GCS score were associated with in-hospital mortality in both the elderly and non-elderly, as well as the overall population. Lower total bilirubin was independently associated with in-hospital mortality in the elderly (aOR 0.34; 95%CI 0.1–0.9; p=0.035), while a higher level was associated with the outcome in the non-elderly. C-reactive protein (CRP) was the only laboratory factor independently associated with all three study outcomes in the elderly (aOR for in-hospital mortality 1.01; 95%CI 1.0–1.0; p=0.006). Conclusion: Important clinical factors associated with in-hospital mortality in elderly COVID-19 patients were age, sex, DNR status, diastolic blood pressure, body temperature, GCS score, total bilirubin, and CRP. These parameters may aid in triage and ED disposition decision-making in this very important patient population during times of limited resources during the COVID-19 pandemic.